Survei Indeks Persepsi Korupsi dan Kepuasan Layanan Balai Litbang Agama Semarang Tahun 2020 - Darwiyanto Darwiyanto (Balai Diklat Keagamaan Semarang, 2021)
The Corruption Perception Index and Service Satisfaction Survey are part of an important area of ​​change in the Integrity Zone Development. This study aims to determine the Corruption Perception Index of the Service Satisfaction at Office of Religious Research and Development, Semarang, Ministry of Religious Affairs in 2020. This study uses a survey method of 150 service users provided by the BLA Semarang. The subjects of this study were users of Religious Research and Development Semarang services in the field of religious education, the field of religious and religious guidance and the field of literature in the field of religion and organizational management. The survey data is processed using simple frequency statistics and described with simple graphs or diagrams and narrative. From the results of this study, the corruption perception index is 3.27 on a scale of 4 and a service satisfaction index of 3.18 on a scale of 4.Based on the results of this study, it is hoped that the Head of the Religious Research and Development can provide guidance to the Religious Research and Development employees, especially in the aspect of officer service in providing solutions to problems faced by users.